Antioxidative Status and Meat Quality Traits as Affected by Dietary Supplementation of Finishing Pigs with Natural Phenolics - Małgorzata Muzolf-Panek; Anita Zaworska-Zakrzewska; Anna Czech; Dariusz Lisiak; Małgorzata Kasprowicz-Potocka (MDPI AG, 2024)
This work investigated the effect of a plant-based phenolic supplement on the color, myoglobin forms, lipid oxidation, and antioxidative status of fresh and stored (10 days at 4 °C) meat (Longissimus thoracis et lumborum), as well as the antioxidative status of the blood and liver. The sensory quality of the meat was also evaluated for color, aroma, texture, juiciness, and palatability. Twenty-four finishing pigs, divided into two groups, were fed a basal diet and a diet with a phenolic supplement (0.1%). The supplementation increased the redness of the meat (+36% for a* and +28% for redness index), the myoglobin (Mb) content (+7%), the antioxidant activity, and the juiciness. The treatment increased the antioxidant status of meat, reflected by superoxide dismutase (SOD) activity and total glutathione (GSH + GSSG). The catalase and SOD activities and GSH + GSSG of the blood and liver were also elevated in the supplemented samples when compared to the control group. A significant effect of time was observed for all tested parameters (pH, color attributes, Mb forms, the antioxidant activity, lipid oxidation) except for the Mb content. For the stored samples, only TBARSs (thiobarbituric acid reagent substances) were affected by the diet. The slope of the plot for TBARS changes with time was significantly different between the control and treated groups (p = 0.017), which indicated a significant effect of dietary supplementation. A higher rate of lipid oxidation was observed in the control samples.